Legal Issues Related to Combating Cybercrime: Experience of the Republic of Kazakhstan - YERJANOV, Timur Keldeshevich; BAIMAGAMBETOVA, Zulfiya Mazhitovna; SERALIEVA, Aliya Mazhitovna; ZHAILAU, Zhanat; SAIRAMBAEVA, Zhuldyz Talgatovna (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017, 2017)
This paper deals with the legal issues related to combating cybercrime in the global information and communication networks through comparative analysis of relevant legislation of the Republic of Kazakhstan and Western European countries. The purpose of this research is to identify the specific features of present cybercrime, to develop a conceptual framework, to specify new forms of cybercrime and to find the main directions in combating cybercrime. The research methodology was based on dialectical, comparative legal, sociological, system-structural and statistical methods, as well as on social experiment. The study gave the possibility to disclose specific features of cybercrime, provided a universal definition of cybercrime, which can be used in international conventions as well as in international criminal investigation. The study highlighted two new types of cybercrime - cyber-terrorism and identity theft with the view of committing crimes, which could be included in the Convention on Cybercrime. The authors of this study developed a universal conceptual framework that can be used in international legal instruments and international cooperation in combating cybercrime and formed a unified approach to address some legal issues related to cybercrime in the global information and communication networks.